2016
DOI: 10.3390/s16081211
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Mass Changes and Crustal Vertical Deformations Constrained by GPS and GRACE in Northeastern Tibet

Abstract: Surface vertical deformation includes the Earth’s elastic response to mass loading on or near the surface. Continuous Global Positioning System (CGPS) stations record such deformations to estimate seasonal and secular mass changes. We used 41 CGPS stations to construct a time series of coordinate changes, which are decomposed by empirical orthogonal functions (EOFs), in northeastern Tibet. The first common mode shows clear seasonal changes, indicating seasonal surface mass re-distribution around northeastern T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…Several recent studies have compared the mass loading signals recorded by GPS and GRACE‐derived displacement (GDD) time series, showing potential for joint interpretation of the two data sets, but all of these studies also reported statistically significant discrepancies. Many of these studies chose regions to perform comparisons with a large loading signal, such as the Amazon basin (Davis et al, ; Fu et al, ; Moreira et al, ), southeast Asia (Fu et al, ; Steckler et al, ), the Nepal Himalaya (Fu & Freymueller, ), southern Alaska (Fu et al, ), West Africa (Nahmani et al, ), Tibet (Pan et al, ), and Greenland (Bevis et al, ). Some studies have also compared GPS and GDD in locations with less extreme loading fluctuations (Gu et al, ; Tregoning et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have compared the mass loading signals recorded by GPS and GRACE‐derived displacement (GDD) time series, showing potential for joint interpretation of the two data sets, but all of these studies also reported statistically significant discrepancies. Many of these studies chose regions to perform comparisons with a large loading signal, such as the Amazon basin (Davis et al, ; Fu et al, ; Moreira et al, ), southeast Asia (Fu et al, ; Steckler et al, ), the Nepal Himalaya (Fu & Freymueller, ), southern Alaska (Fu et al, ), West Africa (Nahmani et al, ), Tibet (Pan et al, ), and Greenland (Bevis et al, ). Some studies have also compared GPS and GDD in locations with less extreme loading fluctuations (Gu et al, ; Tregoning et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the Gravity Recovery and Climate Experiment (GRACE) and the combined loading models (CLMs)-a combination of nontidal atmosphere and ocean loadings and continental water storage loading-have become suitable datasets for modeling VCDs induced by the different surface mass variations. Several studies have been conducted in areas with strong hydrological signals using GRACE and GPS techniques to determine VCDs (see, e.g., Chanard et al 2014;Tiwari et al 2014;Pan et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the vertical crustal deformation throughout Tibet at different spatial and temporal scales (e.g. surface short-term and long-term crustal deformation) brings us new insights on the dynamics of contemporary tectonic processes202122232425. However, how the crustal three-dimensional (3D) deformation varies and the dynamics mechanism of underlying material changes in and around Tibet remains controversy81418.…”
mentioning
confidence: 99%